AN ANALYSIS OF CODE SWITCHING AND CODE MIXING IN CINTA LAURA KIEHL’S VLOG: ‘’CINTA LAURA MEMBANTU ANAK - ANAK MELIHAT DUNIA LEBIH JELAS!’’ - Abdul Muhid Murtadho; Siti Hapipah; Mangangar Sitohang (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
Technological advances have found new ways to express yourself, highlighting your audience more easily. Like making videos that are uploaded to internet sites like YouTube. Uploaded videos are called Vlogs. This is done by Cinta Laura Kiehl in her Video Vlog. Video vlogs can contain works, art, music, and even daily life. the number of celebrities making video vlogs makes the community accept new things, such as the emergence of the phenomenon of using two different languages at one time, or the transfer of one code to another starting to be used by seeing celebrities using or mixing two or more languages in their vlogs. This study examines code switching and code mixing contained in Laura Kiehl's Cinta Laura Kiehl vlog video. The author uses qualitative methods to answer the problem. Therefore, the main purpose of this research is to find out the use of code switching and code mixing, to know the classification of words used and what types of codes are contained in the vlog